Sanksi Pidana pada Hukum Keluarga di Indonesia - Rajafi, Ahmad (Fakultas Syariah IAIN Purwokerto, 2019)
The purpose of a marriage is to form a happy, prosperous and loving family, or in terms of Law No. 1 of 1974 concerning Marriage, is a happy family. The purpose of the marriage will be able to be realized when the people involved in marital practices follow the rules of applicable law and not with an intention to trick or break the law. Because there are persons who commit irregularities in marriage law, progressive and responsive legal breakthroughs are also needed, using local wisdom values that live in the community, namely in the form of criminal sanctions for violators. Criminal sanctions that can be born in family law can be analogous to the penalties that have lived in local communities such as fines, prison rooms and prison villages, and sentences of eviction from their homes to distant places. For this reason, presenting criminal sanctions in Indonesian marriage law is an inevitability.